PENGARUH PEMBERIAN REBUSAN DAUN SELEDRI TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI KELURAHAN MAHAWU KOTA MANADO - Rahmat Ismail; Fitriyana Junaidi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2022)
Hypertension is an abnormal increase in blood pressure in the arteries continuously over a period of time. A person is said to be hypertensive if the systolic blood pressure is equal to or above 140 mmHg and/or the diastolic blood pressure is equal to or above 90 mmHg. The high prevalence of hypertension is one of the problems that affect public health status. The purpose of this study was to determine the effect of giving celery leaf decoction on blood pressure in hypertension patients in Mahawu, Manado This research design is a pre-experimental research design (one-group pre-post test design). The population in this study amounted to 53 patients with the sample used was 17 respondents. The sampling technique used is Accidental Sampling. Data collection using blood pressure observation sheet. The results of the study found that giving boiled celery leaves before giving boiled celery leaves were 12 respondents (70.6%). And after giving boiled celery leaves, 13 respondents (76.5%). The result of p value 0.000 (<0.05) so Ha is accepted. There is an effect of giving boiled celery leaves on blood pressure in hypertensive patients in Mahawu, Manado. The conclusion in this study is that there is an effect of giving celery leaf decoction on blood pressure in hypertension patients in Mahawu, Manado. Suggestions to respondents who often experience hypertension can do their own treatment when high blood pressure by boiling celery leaves.